Development Project Based Learning Model with Performance Assessment Based Ethnoscience to Improve Students' Critical Thinking - Elfrida Elfrida; Nursamsu Nursamsu; Siska Rita Mahyuny; Binari Manurung (Jurnal Penelitian Pendidikan IPA, 2023)
Learning is an interaction between students and educators in a learning environment. The learning process and outcomes are measured using Performance Assessment. The Performance assessment is a suitable tool in biology learning to improve critical thinking skills. this research aimed to develop a project-based learning model with an ethnoscience-based performance assessment and determine the model's practicality for increasing students' critical thinking skills, especially in ethnoscience learning. The method used was a mixed-method design (quantitative and qualitative data) with a research and development model using the 4D model approach (define, design, develop, and disseminate). The research was conducted in SMA Negeri 1 Manyak Panyed, SMA Negeri 2 Patra Nusa, SMA Negeri 1 Langsa, SMA Negeri 5 Langsa, SMA Negeri 1 Sungai Raya and SMA Unggul Aceh Timur. The instruments used were validation sheets by biology lecturers and teachers and students’ questionnaires. The analysis was administrated through Aiken V coefficients for the critical thinking skills test. The results showed that the project-based learning model with an ethnoscience-based performance assessment was effective as a learning tool for students and teachers. In addition, the test of practicality regarding critical thinking skills revealed an improvement in students' knowledge of ethnoscience